Mango: Postharvest biology and biotechnology - Singh, Zora; Singh, R.; Sane, V.; Nath, P. (Taylor & Francis group, 2013)
Mango is one of the choicest fruits in the world and popular due to its delicate taste, pleasant aroma and nutritional value. Mango is indigenous to north-east India and north Burma, but now grown in over 90 countries. In the past two decades, mango production has increased appreciably with international trade jumping approximately four-fold valued close to US$ 950 million. Mango belongs to the category of climacteric fruits and its ripening is initiated and proceeded by a burst in ethylene production and a dramatic rise in the rate of respiration. Although there are a few hundred mango cultivars grown in the Indian subcontinent and other parts of the world, the most popular cultivars are generally highly perishable and ripen within 7 to 9 days of harvest at ambient temperature. Currently, the export potential and international trade of mango is limited due to several factors such as its perishable nature, disease and pest infestation, and susceptibility of certain premium cultivars to chilling injury when stored at low temperatures. Efforts are ongoing to develop technologies for improved storage and packaging, and overcome limitations encountered during storage and transit. Controlled atmosphere (CA) and hypobaric storage of mango are powerful means to overcome its perishable nature.The composition of CA varies among cultivars to ensure its original taste, flavor and aroma. Edible coating on the fruit skin may further cut down the rate of deterioration. Recently, significant advances have been made in understanding ripening characteristics of mango at the molecular level. Candidate genes related to ethylene biosynthesis and signalling, cell wall modification, aroma production and stress response have been cloned and characterized for future use in mango improvement. Efforts are also being made to establish a suitable transformation and plant regeneration system so that transgenic mango with added value and increased shelf life for long distance transportation could be developed.